ULTRASONIC POSSIBILITIES OF DIAGNOSING CHANGES IN KIDNEYS OF CHILDREN WITH ALAGILLE SYNDROME - M. I. PYKOV; E. A. ILIPPOVA; V. E. RYCHKOVA; A. V. DEGTYAREVA,; A. A. PUCHKOVA (Медицинский совет, 2017)
The article shares the results of a follow-up of children with Alagille syndrome in the first year of life and signs of neonatal cholestasis. Diagnostic criteria of ultrasonic kidney changes in children with Alagille syndrome and their relationship with biochemical parameters of blood serum are defined. The authors tell about a new method of ultrasound kidney examination using conventional technique involving a linear high-frequency transducer, which contributes to early diagnosis of the disease